Faktor yang Mempengaruhi Purchase Intention terhadap Consumer Purchase Behavior pada Healthy Food Restaurant - Varez Widharto Mahdi; Mohamad Rizan; Usep Suhud (Indo Publishing, 2026)
This study aims to analyse the influence of Attitude, Perceived Behavioural Control, and Health Consciousness on Purchase Intention, as well as the influence of Purchase Intention on Consumer Purchase Behaviour among consumers of Burgreens healthy food products in Jakarta. The research framework is based on an adapted or extended Theory of Planned Behaviour. Attitude and Perceived Behavioural Control are constructs derived from the Theory of Planned Behaviour (TPB), while Health Consciousness is positioned as an additional variable relevant to the context of healthy food purchases. The model does not include Subjective Norm and therefore does not represent all of the original TPB constructs. Purchase Intention is limited to the intention to buy or consume Burgreens healthy food products, while Consumer Purchase Behaviour describes the purchasing behaviour reported by respondents. The study employs a quantitative approach, an explanatory design, a cross-sectional survey, purposive sampling, a six-point Likert scale, and covariance-based Structural Equation Modelling using AMOS. Respondents must be at least 17 years old, reside in one of the five administrative districts of Jakarta, have purchased or consumed Burgreens products within the past three months, and be willing to complete an online questionnaire. Four hypotheses test the pathways X1→Z, X2→Z, X3→Z, and Z→Y. As this research is still in the proposal stage, it does not yet present empirical results.